The role of soils on pteridophyte distribution in tropical American forests - Gabriel Massaine Moulatlet; Gabriela Zuquim; Hanna Tuomisto (The British Pteridological Society, 2025)
The distributions of plant species are affected by characteristics of their environment, most importantly climate and soils. Ferns and lycophytes (hereafter pteridophytes) are no exception to this general ecological principle. However, until relatively recently, little information has been available about pteridophyte-soil relationships in the tropics. Here we review literature that sheds light on the impact of soil conditions on pteridophyte distribution in the lowland forests of tropical America. We provide examples of both soil-related community-level patterns in species turnover and distributions of individual species and genera along soil gradients. We then discuss the relevance of these patterns for the evolution and diversification of pteridophyte lineages and for practical applications, such as the use of pteridophytes as indicators in classification and mapping of soil-related habitats. Finally, we discuss challenges in filling the gaps of knowledge in pteridophyte-soil relationships and suggest possible solutions for them.